Homeric Effects in Vergil's Narrative - Barchiesi, Alessandro (Princeton University Press, 2015)
Cover -- HOMERIC EFFECTS IN VERGIL'S NARRATIVE -- Title -- Copyright -- Contents -- Foreword -- Introductory Note -- 1 THE DEATH OF PALLAS: Intertextuality and Transformation of the Epic Model -- 2 THE STRUCTURE OF AENEID 10 -- 3 THE ARMS IN THE SKY: Diffraction of a Narrative Theme -- 4 THE DEATH OF TURNUS: Genre Model and Example Model -- APPENDIX -- APPENDIX: The Lament of Juturna -- AFTERWORD -- NOTES -- WORKS CITED -- SELECT INDEX -- SELECT INDEX LOCORUM -- INDEX OF MODERN AUTHORS.